The Term Structure of Expected Recovery Rates - Doshi, Hitesh; Elkamhi, Redouane; Ornthanalai, Chayawat (Journal of Financial and Quantitative Analysis, 2018)
There is widespread agreement that corporate debts’ recovery rates are time varying, but empirical work in this area is limited. We show that the joint information from the term structure of senior and subordinate credit default swaps can identify the level and the dynamics of recovery rates. We estimate a reduced-form no-arbitrage model on 46 firms across different industries. We find that the term structure of expected recovery rates is, on average, downward sloping. However, an inversion occurs during the 2008 crisis, suggesting the market expects higher recoveries conditional on short-term survival. The inversion is more pronounced for firms in distressed industries.